Propofol and Nigella sativa L Seeds Ethanol Extract Enhance Neuroprotection: A Histopathological Study in Rat Models with Traumatic Brain Injury - Kulsum Kulsum; Syahrul Syahrul; Kartini Hasballah; Ummu Balqis (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Nigella sativa has been known for its neuroprotective properties, while propofol is an anesthetic induction drug that has been widely used in the treatment of traumatic brain injury (TBI). To determine the effectiveness of both active ingredients, it is necessary to compare their neuroprotective effects. This study was performed since not many studies have compared the effect of propofol and Nigella sativa seeds ethanol extract (NSSEE) or their combination on histopathological features in TBI cases.METHODS: Thirty male rat models were divided into 5 groups. Four groups received TBI induction with the methods of Feeney’s weight drop model, while another group (control group) did not receive TBI induction. Groups with TBI induction, later received no treatment, treatment with 500 mg/kg NSSEE orally, 10 mg/kg propofol intravenously, or a combination of NSSEE and propofol. After 8 days, rats were euthanized by cervical dislocation. Subsequently, a craniotomy was performed to obtain brain samples. The brain sample was placed in 10% neutral buffered formalin for histopathological examination, which includes brain hemorrhage, congestion, inflammatory cells, necrosis, apoptosis, and degeneration.RESULTS: The present study found that NSSEE showed greater efficacy in histopathological features (brain hemorrhage, congestion, inflammatory cells, necrosis, apoptosis, and degeneration) in rat models with TBI compared to propofol or a combination of propofol and NSSEE.CONCLUSION: NSSEE has superior potential compared to propofol and the combination of both in providing neuroprotection in TBI cases.KEYWORDS: traumatic brain injury, propofol, Nigella sativa seeds ethanol extract, histopathology, neuroprotective